Individual ideology and biased perceptions of income - Marius R. Busemeyer; Nathalie Giger; Nadja Wehl (University of Konstanz, Cluster of Excellence "The Politics of Inequality", 2024)
In this paper, we focus on individuals' perceptions of their own position within the income distribution and argue that ideological biases influence these perceptions. In particular, we take into account the two-dimensional ideological space of European party systems and develop arguments about social class mis-identification (economic dimension) and cultural threat and privilege (cultural dimension) leading to either over- or underestimation. We use novel survey data from the Konstanz Inequality Barometer (2020 and 2022) and find that socially conservative individuals are more likely to underestimate their relative income position, i.e. they perceive themselves to be worse off than they are. By contrast, individuals with a rightist position on the economic ideology are more likely to overestimate their relative position. These biases have downstream consequences for electoral behavior as well. Our findings have important consequences for our understanding of individuals' perceptions of inequality but also, more broadly, for the politics of redistribution.
urn:nbn:de:bsz:352-2-rvbni2x6a2ay1
Keywords: 320